An Unusual Case of Headache: Isolated Fungus Ball in Concha Bullosa. Issue 6 (September 2018) - Bulut, Fuat; Kazikdas, Kadir Cagdas
Abstract : Abstract: A concha bullosa forms when the middle turbinate becomes pneumatized, which is a common anatomic variation; however, fungus ball in concha bullosa is rather rare. An otherwise healthy 52-year-old man presented to our ear, nose and throat clinic with the complaints of midfacial pressure headache and malodorous postnasal drip. Computed tomography of the paranasal sinuses demonstrated a polypoid hyperdense lesion with slight microcalcifications in the right nasal cavity, accompanied with a complicated fluid collection in the right frontoethmoideal recess seen as hypodensity in contrast to this hyperdensity. The histopathological examination reported a fungal infection. We present an extremely rare case of isolated fungal mass in the right middle concha detected in an early stage without any evidence of fungal infection of the other paranasal sinuses and discuss the importance of reevaluation of the computed tomography scans in suspicion of a fungal sinusitis.